Potential toxicity effects of Anastatica hierochuntica aqueous extract on prenatal development of Sprague-Dawley rats - Md Zin, Siti Rosmani; Kassim, Normadiah M.; Mohamed, Zahurin; Fateh, Abdulmannan H.; Alshawsh, Mohammed Abdullah (Elsevier, 2019)
Ethnopharmacological relevance: Anastatica hierochuntica (A. hierochuntica) is a plant consumed in folk medicine for the treatment of reproductive system related problems and metabolic disorders. It is of concern that the herb is commonly consumed by pregnant women towards the end of pregnancy to ease the process of labour, despite the lack of studies evaluating its safety. Aim of this study: This study aimed to investigate the potential toxicity effects of A. hierochuntica in pregnant Sprague-Dawley rats and their developing foetuses. Materials and methods: Experiments were conducted in accordance to the Organisation for Economic Co-operation and Development guideline 414. Animals were randomly divided into four groups (n = 10 females per group): negative control (received the vehicle only), experimental animals received 250, 500, and 1000 mg/kg A. hierochuntica aqueous extracts (AHAE), respectively. Treatment was administered daily by oral gavage from gestational day (GD) 6–20, and caesarian section performed on GD21. Results: There were significant reduction in the corrected maternal weight gain of dams and body weight of foetuses in the lowest and highest dose of AHAE-treated animals compared to the control. These findings were associated with the increase in anogenital distance index and multiple congenital anomalies observed in some of the offspring. On the other hand, rats treated with 500 mg/kg showed higher embryonic survival rate with absence of significant treatment-related effect. Conclusion: Findings showed that highest and lowest doses of AHAE have prenatal toxicity effects in SD rats. Therefore, AHAE is potentially harmful to the developing foetuses especially when consumed during the period of implantation and organogenesis. As for the rats treated with 500 mg/kg AHAE, there was no significant treatment-related effect. Hence, we postulate that this finding suggests that the disruption on the hormonal regulation could have been compensated by negative feedback response. The compensated effects of AHAE at 500 mg/kg and the presence of lowest observed adverse effect level (LOAEL) at 250 mg/kg has resulted in a non-monotonous dose response curve (NMDRC), which complicates the determination of the value of no-observed-adverse effect level (NOAEL). © 2019 Elsevier B.V.